(untitled) (Biological Sciences - PJSIR, 2002)
Some heavy metals (Pb,Ni,Fe,Cu,Zn,Cd ,Co,Mn,and Cr) were determined in Oreochromis niloticus, Clarias gariepinus and Synodontis spp obtained from the coastal water of Ondo State. All metals examined and detected in all fish samples. Iron, manganese and cadmium were found to be the most abundant metals in the fish samples with an average values of 35.8, 31.3, and 12.5 mg kg·1 respectively. Except for manganese, iron and cadmium , Syndrontis spp has the highest concentration for virtually all the metals under examination.